PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Silvia Megawati, 09.05.52.0126; Badjuri, Achmad (Students Journal of Accounting and Banking, 2013)
The objective of this study is to examine the influence of institutional ownership, managerial ownership, foreign ownership, board of commissioner, independent Commissioner, audit Committee, company size, corporate social responsibility among manufacturing sector which listed on Indonesia Stock Exchange. The population is 146 companies of manufacturing sector which listed on Indonesia Stock Exchange at period 2009 to 2011. Sample was choose using purposive sampling method amount to 19 companies. Technique test of data is by using multiple linear regression. These results indicate that managerial ownership, board of commissioner, and company size is significant positively influence the corporate social responsibility disclosure, Institutional ownership, foreign ownership, independent Commissioner, audit Committee, isnât influence the corporate social responsibility disclosure at all.Keywords: influence of institutional ownership, managerial ownership, foreign ownership, board of commissioner, independent Commissioner, audit Committee, company size, and corporate social responsibility disclosure.